EP.FRI.8 Hajibandeh index predicts nature of peritoneal contamination and risk of postoperative mortality in patients with acute abdominal pathology: A multicentre cohort study. (28th October 2021) - Hajibandeh, Shahab; Hajibandeh, Shahin; Shah, Jigar; Mansour, Moustafa
Abstract: Aims: To develop and validate intraperitoneal contamination index, Hajibandeh Index (HI), derived from combined levels of CRP, lactate, neutrophils, lymphocytes and albumin in predicting the nature of peritoneal contamination and risk of postoperative mortality in patients with acute abdominal pathology. Methods: A multicentre cohort study was conducted to develop and validate an index to predict presence of purulent and feculent contamination and risk of postoperative mortality in patients with acute abdominal pathology. All adult patients with acute abdominal pathology requiring emergency laparotomy between 2014 and 2020 were included. The index was developed in a primary cohort and was validated in retrospective and prospective validation cohorts. ROC curve analysis was performed to determine discrimination of the index and cut-off values of HI that could predict nature of peritoneal contamination and postoperative mortality. Results: 737 patients were included (234 in primary cohort, 234 in retrospective validation cohort, and 269 in prospective validation cohort). The analyses identified HI of 24.76 as cut-off value for purulent contamination (AUC:0.78, P<0.0001;sensitivity:82.4%, specificity:60.9%); HI of 33.84 as cut-off value for feculent contamination (AUC:0.78, P<0.0001;sensitivity:82%, specificity:67.8%), and HI of 33.47 as cut-off value for postoperative mortality (AUC:0.70, P<0.0001;sensitivity:72.7%, specificity:58.47%). The results of the primary cohort and validation cohorts were comparable. Conclusions: HI predicts presence of purulent and feculent contamination in patients with acute abdominal pathology and risk of postoperative mortality in patients undergoing emergency laparotomy. Future studies should investigate the effect of HI on accuracy of preoperative prognostic scoring tools and on patient selection for operative or non-operative management of underlying abdominal pathology.